Characteristics the Backline and Unyeng-unyeng of Swamp Buffalo on Kabaena Island, Bombana Regency - Masyudin Masyudin; La Ode Nafiu; Nur Santy Asminaya (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
This study aimed to analyze the qualitative characteristics of the mud buffalo (Swamp buffalo) at different ages on Kabaena Island, Bombana Regency. Determining the research location was carried out by purposive sampling on Kabaena Island. The data obtained were analyzed descriptively. The results showed that the qualitative characteristics of Bali cattle in Central Kabaena District, Bombana Regency were: the dominant dorsal line was a flat back line with a percentage of 68.18%, the dominant unyeng-unyeng on the head with a percentage of 51.52%, the shape of mud buffalo horns which dominant namely kerung horn with a percentage of 65.15%. It can be concluded that the qualitative characteristics of the mud buffalo on Kabaena Island, Bombana Regency, are still diverse.